Impact of workplace smoke-free policy on secondhand smoke exposure from cigarettes and exposure to secondhand heated tobacco product aerosol during COVID-19 pandemic in Japan: the JACSIS 2020 study - Takahiro Tabuchi; Koji Kawakami; Kota Katanoda; Satomi Yoshida; Koichiro Takenobu (BMJ Open)
Objectives Promoting smoke-free policies is a key intervention for reducing secondhand smoke (SHS) exposure. During the COVID-19 pandemic in Japan, many indoor smoking spaces in workplaces were closed. This study aimed to reveal the association between a workplace smoke-free policy and SHS exposure among non-smoking employees, distinguishing between SHS exposure from cigarettes and exposure to secondhand heated tobacco product (HTP) aerosol, which have recently become popular in Japan.Design and setting We used data from the Japan COVID-19 and Society Internet Survey conducted in August–September 2020.Participants Among the 25 482 eligible respondents, 8196 non-smoking employees were analysed.Primary outcome measure Multivariable logistic regression models were used to examine the impact of smoke-free policies in the workplace.Results Compared with complete smoking bans, the ORs and 95% CIs for workplace SHS exposure at least once a week from cigarettes were 2.06 (95% CI: 1.60 to 2.65) for partial bans with no longer available smoking spaces, 1.92 (95% CI: 1.63 to 2.25) for partial smoking bans with still available smoking spaces and 5.33 (95% CI: 4.10 to 6.93) for no smoking bans. The corresponding ORs and 95% CIs for exposure to secondhand HTP aerosol were 4.15 (95% CI: 3.22 to 5.34), 2.24 (95% CI: 1.86 to 2.71) and 3.88 (95% CI: 2.86 to 5.26), respectively.Conclusions The effect of partial bans was limited, and temporary closure of smoking spaces might contribute to increased exposure to secondhand HTP aerosol. Complete smoking bans in the workplace were reaffirmed to be the best way to reduce SHS exposure from cigarettes and exposure to secondhand HTP aerosol.